Transistor Application of Phenacene Molecules and Their Characteristics. Issue 24 (22nd July 2014) - Kubozono, Yoshihiro; He, Xuexia; Hamao, Shino; Teranishi, Kazuya; Goto, Hidenori; Eguchi, Ritsuko; Kambe, Takashi; Gohda, Shin; Nishihara, Yasushi
Abstract: The characteristics of field‐effect transistors (FETs) fabricated from thin films and single crystals of phenacene molecules are fully reported in this review together with the electronic and crystal structures of phenacenes. Phenacene molecules possess a low HOMO level and a wide band gap. The highest mobility observed in the phenacene thin‐film FETs is 7.4 cm 2 V –1 s –1 for [6]phenacene, and in single‐crystal FETs the highest value is 6.3 cm 2 V –1 s –1 for [7]phenacene. The phenacene thin‐film FETs show O2 ‐sensing properties unlike their single‐crystal FETs. The bias‐stress effect is fully investigated for phenacene single‐crystal FETs. Furthermore, the low‐voltage operation of phenacene single‐crystal FETs with electric‐double‐layer (EDL) capacitors is reported. The temperature dependence of phenacene single‐crystal FETs is reported to clarify the transport mechanism, which is suggestive of band‐like transport. Abstract : Field‐effect transistors (FETs) can be fabricated with thin films and single crystals of phenacene. The excellent p‐channel FET characteristics that have been found by our group are fully reported in this review.